2015
DOI: 10.1128/ec.00116-15
|View full text |Cite
|
Sign up to set email alerts
|

ERG2 and ERG24 Are Required for Normal Vacuolar Physiology as Well as Candida albicans Pathogenicity in a Murine Model of Disseminated but Not Vaginal Candidiasis

Abstract: Several important classes of antifungal agents, including the azoles, act by blocking ergosterol biosynthesis. It was recently reported that the azoles cause massive disruption of the fungal vacuole in the prevalent human pathogen Candida albicans. This is significant because normal vacuolar function is required to support C. albicans pathogenicity. This study examined the impact of the morpholine antifungals, which inhibit later steps of ergosterol biosynthesis, on C. albicans vacuolar integrity. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 63 publications
0
26
0
1
Order By: Relevance
“…We previously reported that the vps21⌬/⌬ mutant exhibits enhanced growth in the presence of the azole antifungals versus wild-type (WT) controls, despite ergosterol depletion (9). We therefore examined plasma membrane integrity following azole treatment using a luciferasebased assay (15) to determine if the vps21⌬/⌬ mutant exhibited signs of membrane damage. A cytoplasmic version of nanoluciferase (Nluc; Promega Corp.) (23) was expressed in mutant and control strains (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that the vps21⌬/⌬ mutant exhibits enhanced growth in the presence of the azole antifungals versus wild-type (WT) controls, despite ergosterol depletion (9). We therefore examined plasma membrane integrity following azole treatment using a luciferasebased assay (15) to determine if the vps21⌬/⌬ mutant exhibited signs of membrane damage. A cytoplasmic version of nanoluciferase (Nluc; Promega Corp.) (23) was expressed in mutant and control strains (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12,62 Mechanisms of immunoprotection are still debated, and the factors that trigger the transition from commensal to pathogenic yeast are still obscure. However, it is generally accepted that predispositions for Candida growth/invasion are niche specific 63,64 , though immune defects, breaches in epithelial integrity and microbial dysbiosis are common themes. 55 While many similarities exist between the mucosal environments of the mouth and vagina, the immunology of Candida vaginitis is undoubtedly distinct.…”
Section: Pathogenesis Of Candida and Vulvovaginal Candidiasismentioning
confidence: 99%
“…In the context of differences between mucosal and invasive Candida infections, it is of interest to mention a recent study by Luna‐Tapia et al. , which indicated that ERG2 and ERG24 are required for pathogenicity of C. albicans in experimental mouse systemic infection but not vaginal. Another recent study by Moyes et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that Price 25 reported that blood isolates produced much higher levels than isolates from wounds or urine. In the context of differences between mucosal and invasive Candida infections, it is of interest to mention a recent study by Luna-Tapia et al [49], which indicated that ERG2 and ERG24 are required for pathogenicity of C. albicans in experimental mouse systemic infection but not vaginal. Another recent study by Moyes et al [50] described a toxin, candidalysin, which is critical for mucosal infection and elucidates mucosal pathogenesis.…”
Section: Discussionmentioning
confidence: 99%